Nutrition in HNSCC: is it a matter for oncologists? The role of multidisciplinary team—a narrative literature review - Denaro, Nerina; Bareggi, Claudia; Galassi, Barbara; Beltramini, Giada; Wekking, Demi; Proh, Michele; Ibba, Tullio; Solinas, Cinzia; Garrone, Ornella (Frontiers in Oncology, 2024)
Background: Malnutrition, defined as weight loss and unsatisfactory nutrient intake, is very common in patients with HNSCC either in the early and in the palliative settings. Despite increased awareness, nutritional programs are not yet adequately implemented in these patients. There are several reasons for this delay: among them, differences in composition, the expertise of the multidisciplinary teams involved in HNSCC patients' treatment and economic and network resources conditioning faster or slower nutritional supplies delivery. This situation affects the outcomes and the quality of life of HNSCC patients. Materials and Methods: We investigated available literature about nutritional support in HNSCC patients, its impact on outcomes, prognosis, and on quality of life, and we focused on the role of the multidisciplinary team. We revised 8491 articles, and after the exclusion of duplicates and of manuscripts not written in English, 1055 were analysed and 73 were deemed eligible for the present work. Results: After literature review we can state that malnutrition, sarcopenia, and cachexia are associated with systemic inflammation and closely correlated with poor outcomes. An evaluation of the nutritional status of the multidisciplinary team pre, during and after therapy could improve the patients as the goal of the therapeutic approach is widely designed.Conclusions: We suggest that the treatment workflow definition is fundamental to propose a tailored nutritional approach for HNSCC Patients with benefits on outcomes and quality of life. These results could be achieved by a multidisciplinary team